TURNOVER INTENTION YANG DIPENGARUH OLEH JOB INSECURITY DAN JOB MOTIVATION - Indarta Priyana; Vinna Permanawati; Sabilla Saberina (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to explain the effect of job insecurity and job motivation variables on turnover intention in the warehouse division of PT Padjadjaran Internusa textile Bandung branch. The phenomenon that occurs is that the turnover intention rate in the company is high, namely 18.82% in 2020. This study aims to determine the general description of job insecurity, job motivation, and turnover intention. Knowing how much influence job insecurity has on turnover intention, job motivation on turnover intention, and knowing how much influence job insecurity and job motivation have on turnover intention. The research method used is descriptive and verification method with a quantitative approach. The tool for data collection uses a questionnaire distributed to 46 employees in the division of PT Padjadjaran Internusa textile Bandung branch by using non-probability sampling technique, saturated sample. The results of the analysis of job insecurity and job motivation on turnover intention have an effect of 18.10% while the remaining 81.90% (100% -18.10%) is influenced by other variables not explained in this study. The results of multiple linear regression analysis show that simultaneously and partially job insecurity and job motivation have a significant effect on turnover intention, this is indicated by the results of the simultaneous test that a significance value of F is 0.102 which is greater than of 0.05 (0.014 <0 ,05). The significance value is above 5% resulting in the decision Ha is accepted and Ho is rejected. The results of the partial test for the job insecurity variable obtained a significance value of t of 0.033 which is smaller than 0.05 (0.033 <0.05) so that the decision Ha is accepted and Ho is rejected. The job motivation variable is 0.041, which is smaller than 0.05 (0.041 <0.05), resulting in the decision that Ha is accepted and Ho is rejected